2021
DOI: 10.1186/s12995-021-00305-3
|View full text |Cite
|
Sign up to set email alerts
|

Adverse health manifestations in the hands of vibration exposed carpenters - a cross sectional study

Abstract: Background Despite EU regulatory standards, many workers suffer injury as a result of working with hand-held vibrating tools. Our aim of this study was to confirm whether carpenters, a highly exposed group, suffer more injuries to their hands than painters, a group assumed to be less exposed to vibration. Methods 193 carpenters (participation rate 100%) and 72 painters (participation rate 67%), all men, answered a questionnaire and underwent a clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 53 publications
0
7
0
2
Order By: Relevance
“… 15 The use of 2PD has been questioned 5 , 21 but has also been reported to provide valuable information. 22 A recent study by Tekavec et al concludes that diminished perception of touch and vibrotactile perception are the most common clinical findings in vibration exposed carpenters and painters. 22 In this study, all four SEMs are used in conjunction, as described in the National guidelines, with the alternation that vibrotactile perception was examined with the more advanced Vibrosense equipment instead of tuning fork.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 15 The use of 2PD has been questioned 5 , 21 but has also been reported to provide valuable information. 22 A recent study by Tekavec et al concludes that diminished perception of touch and vibrotactile perception are the most common clinical findings in vibration exposed carpenters and painters. 22 In this study, all four SEMs are used in conjunction, as described in the National guidelines, with the alternation that vibrotactile perception was examined with the more advanced Vibrosense equipment instead of tuning fork.…”
Section: Introductionmentioning
confidence: 99%
“… 22 A recent study by Tekavec et al concludes that diminished perception of touch and vibrotactile perception are the most common clinical findings in vibration exposed carpenters and painters. 22 In this study, all four SEMs are used in conjunction, as described in the National guidelines, with the alternation that vibrotactile perception was examined with the more advanced Vibrosense equipment instead of tuning fork. Rolke et al found that a 64 Hz tuning fork was the most sensitive instrument to detect sensory loss in HAVS in comparison with monofilament and cold and warm detection thresholds in a population of mainly lumberjacks.…”
Section: Introductionmentioning
confidence: 99%
“…A thorough and variable assessment strategy tailored to each patient can significantly enhance the recognition of underlying pathologies. This approach not only aids in diagnosing the cause of pain and dysfunction but also strengthens the patient-physician relationship by providing clarity and reassurance to the patient (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…The hand-held power sander is a frequently used tool in woodworking, and it is a significant source of risk in terms of dust [6][7][8][9][10][11][12], vibration [13][14][15][16][17], and, not least, noise [18][19][20][21]. The noise reduction of a hand-held electric sander is an integral part of the design process and is achieved particularly by applying measures at the source to control noise.…”
Section: Introductionmentioning
confidence: 99%